Scrofuloderma: a diagnostic challenge - Renan Bernardes de Mello; Everton Carlos Siviero do Vale; Isabela Guimarães Ribeiro Baeta (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Cutaneous tuberculosis is a rare form of extrapulmonary tuberculosis, comprising 1-2% of cases. Caused by Mycobacterium tuberculosis or related strains, it presents a wide range of clinical manifestations, mimicking other chronic dermatoses and leading to delayed diagnosis. A case of scrofuloderma is reported, whose diagnosis and treatment were only made six years after onset of the disease.